Construction and evaluation of Brassica rapa orphan genes overexpression library - Mingliang Jiang; Mingliang Jiang; Zongxiang Zhan; Xiaonan Li; Zhongyun Piao (Frontiers in Plant Science)
Orphan genes (OGs) are crucial for species-specific characteristics and stress responses and are restricted to a specific taxon. However, their functions within particular species are poorly understood. Previous research identified OGs in Brassica rapa (BrOGs). In this study, the BrOGs overexpression (BrOGsOE) library in Arabidopsis thaliana was constructed. Approximately 128 unknown functional BrOGs were selected from Chinese cabbage and were overexpressed. The analysis focused on the phenotypes of leaf morphology and flowering time against phenotypic differences between Chinese cabbage and Arabidopsis. Interestingly, 72.66% of the transgenic lines showed distinctive phenotypic changes. Chinese cabbage-specific features, including curved, hairy, upward or downward-curving leaves, serrated margins, and multiple leaves, were observed in the BrOGsOE lines. The BrOGs overexpression library was associated with numerous variations in flowering time, particularly delayed flowering. This suggested that the delayed flowering time caused by BrOGs may be associated with resistance to bolting seem in Chinese cabbage. Furthermore, the results of stress treatment of 24 BrOGsOE lines with no apparent significant phenotypes suggested that a number of BrOGs have both general and specific functions against environmental and pathogenic stress. The findings of this study provide a comprehensive overview of the roles of BrOGs, emphasizing their significance as a resource for identifying positive genes associated with species-specific characteristics and stress responses and offering a solid foundation for the functional analysis of BrOGs.